Management of Road Intersection and Performance of Intelligent Traffic Control Systems Nairobi County, Kenya - Chege, Margaret; Gakuu, Christopher; Mbugua, John (Journal of Public Policy and Administration, 2025)
Purpose: This study aims to explore the factors influencing the performance of Intelligent Traffic Control Systems (ITCS) in Nairobi, focusing on road intersection management, traffic education, law enforcement, and evaluation, while examining how these factors interact to enhance ITCS performance. Methodology: A pragmatist research paradigm was adopted, integrating qualitative and quantitative approaches. A mixed-methods, explanatory research design was used to provide comprehensive insights into traffic management practices, combining qualitative stakeholder interviews with quantitative survey data. The study targeted 942 traffic management stakeholders, including public service vehicle SACCO leaders, traffic police officers, county officials, and representatives from the National Transport and Safety Authority (NTSA) and the Kenya Urban Roads Authority. Data collection involved key informant interviews and structured questionnaires to capture diverse viewpoints and enhance the study’s comprehensiveness. Findings: The results reveal that traffic education positively impacts ITCS performance, emphasizing the importance of educating road users to improve traffic flow. However, road intersection engineering and law enforcement showed minimal effect on ITCS, and traffic evaluation had a negative impact on performance. This suggests that while traffic education is critical, infrastructure and enforcement need further improvement for better results. Unique Contribution to Practice and Policy: This study offers insights into factors affecting ITCS performance and provides practical recommendations for policymakers, emphasizing the need to focus on enhancing traffic education, improving infrastructure, and optimizing law enforcement to strengthen traffic management systems in Nairobi. An integrated ap